CHRISTIAN WORSHIP: THE ‘LITURGY OF LIFE’ IN THE ‘HEART OF THE WORLD’ - Kalliath, Antony (Journal of Dharma, 2006)
While reflecting on the ‘thing’ (res) and tenor of worship in the present day life I, living in Bangalore, find the initiatives of this modern city a relevant point of departure. It is, now, no more religious centres like Banaras or Saranat, but cities like Bangalore and Delhi that offer what is called ‘the vision thing’ to the ongoing silent redefinition of the culturalscape of the new politically and economically resurgent India. To its credit, Bangalore is known as a city of IT, Bio-Tech, Fashion, apart from its customary titles, like ‘garden city’ or ‘silk-city’. It is now becoming a hub of spiritual initiatives and adventures inviting attention on a national level and beyond. Recently, in connection with the 50th birthday celebrations of their renowned guru Sri Sri Ravishankar, about a half a million people from every corner of the globe flocked just to ‘breathe’ (even though Bangalore is quite infamous for its pollution!). Bangalore is a home of the world famous gurus, Sri Satya Sai Baba and Sri Sri Ravishankar. While the former translates worship in terms of ‘prema’ (pure love) the latter sees ‘breathing’ (sudarsanakriya) which envisions a new paradigm of spiritual life known as “Art of Living.” In this context a mention must also be made on another renowned living saint of global following, Mata Amrtanandamayi who sees worship as “hugging” (vatsalya, motherly love of God), and considers herself as the instrument of God, leading people to Divine vatsalya. Thus, we find different redefinitions of worship in the ongoing initiatives of spirituality, like ‘prema’, ‘sudarsanakriya’, or ‘vatsalya’ which look palatable to the modern wo/man while s/he finds it hard to strike a balance between peace and pace of the high-tech fast-track life.